LANGUAGE LEARNING STRATEGIES USED BY MALE AND FEMALE STUDENTS OF INTERNATIONAL UNDERGRADUATE PROGRAM OF FACULTY OF ADMINISTRATIVE SCIENCE UNIVERSITAS BRAWIJAYA - SHOLICHAH, HIDAYATUS (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study is designed to figure out the degree of learning strategies applied by2012 academic year students of International Undergraduate Program of Facultyof Administrative Science. It also examined the significant relationship betweengender and the choice of language learning strategies used by 2012 academic yearstudents of International Undergraduate Program of Faculty of AdministrativeScience. The participants of this study were 31 students including 12 male and 19female students. The findings revealed that students mostly used metacognitivestrategies compared with other strategies. On the other hand, memory strategieswere the lowest frequently used ones. Furthermore, although there are differencesin the mean score for the overall language learning strategies used by male andfemale students, the statistical t-test and chi-square result showed that there is nostatistically significant difference in learning strategies used by male and femalestudents. It means that there is no significant correlation between genderdifferences and the choice of language learning strategies.Key words: Language Learning Strategies, Gender, and Strategy Inventory for Language Learning (SILL)